Experience capitalization: Writing for those who'll read - Ostroski, Dirce (Technical Centre for Agricultural and Rural Cooperation, 2019)
An experience capitalization process is a short, practical, effective and simple process, and its final product is a document which is complete. It is possible to focus on activities within the farm of a single, small-scale producer, as well as to capitalize a broad programme involving, let's say, 500 communities. This is one of the things that makes the methodology very attractive. Moreover, a capitalization process includes the analysis of both negative and positive aspects in a particular experience, and draws lessons from them. This brings us a step beyond the systematisation processes we are familiar with in the Brazilian Semiárido.